This question is incomplete but we can take "y(x)=\\lambda \\int_{0}^{1} e^{x+1} y(t) d t" to understand the problem.
The given equation can be written as
"y(x)=\\lambda e^{x} \\int_{0}^{1} e^{t} y(t) d t \\ldots(\\mathrm{i})"
Assume that "\\quad C=\\int_{0}^{1} e^{t} y(t) d t \\ldots(\\mathrm{ii})"
Then, from Eq. (i), we have "u(x)=\\lambda C e^{x} \\ldots . . (iii)"
"\\Rightarrow y(t)=\\lambda C e^{t}"
Putting this value in eq. (ii), we get
"\\begin{aligned}\n&C=\\int_{0}^{1} e^{t}\\left(\\lambda C e^{t}\\right) d t=\\lambda C\\left[\\frac{e^{2 t}}{2}\\right]_{0}^{1} \\\\\n&\\Rightarrow C=\\frac{\\lambda C}{2}\\left(e^{2}-1\\right) \\Rightarrow C\\left[1-\\frac{\\lambda}{2}\\right]\\left(e^{2}-1\\right)=0\n\\end{aligned}"
If "\\mathrm{C}=0" , then Eq. (iii) gives "{y}({x})=0" .
We, therefore assume that for non-zero solution of Eq. (i).
If "C \\neq 0" , then Eq. (iii) gives
"1-\\frac{\\lambda}{2}\\left(e^{2}-1\\right)=0"
"\\Rightarrow \\lambda=\\frac{2}{e^{2}-1}"
Which is an eigen value of Eq. (i).
To find the corresponding eigen function, putting the value of "\\lambda" in Eq. (iii), we get
"y(x)=\\frac{2 C}{e^{2}-1} \\cdot e^{x}"
The eigen function is "\\mathrm{e}^{{x}}."
Comments
Leave a comment